Perbandingan Kompres Hangat dan Kompres Dingin terhadap Respon Nyeri Imunisasi Pentabio di Wilayah Puskesmas Pekauman Banjarmasin - Agustin Criselly Leluni; Novalia Widiya Ningrum; Hairiana Kusvitasari (Al-Hayat: Natural Sciences, Health & Environment Journal, 2024)
Immunization is an effort to provide immunity to babies and children by maintaining vaccines in the body to produce antibodies to prevent certain diseases. Providing complete basic immunization aims to obtain initial active immunity including, among others, BCG (Bacillus Calmette-Guerin), Diphtheria, Pertussis, Tetanus, Hemophilus Influenza type B (Hib), Hepatitis B, Polio and Measles. Pain is defined as an uncomfortable sensation and emotional experience associated with actual or potential tissue damage, thus the importance of evidence-based immunization used to reduce pain. Pain management with compresses can be done before immunization at the injection area is considered to be able to reduce pain in babies. Warm compresses can cause a heat effect which will be absorbed into body tissue and can reduce pain. Cold compresses can make the skin reduce its pain response due to the release of endorphins which can block the transmission of nerve fibers. The aim of this research is to determine the comparison of the use of warm compresses and cold compresses on the pain response to pentabio immunization in the Pekauman Community Health Center area. The method used is Pre-Experimental Design with sampling using Nonprobability Sampling. The results of the Mann-Whitney test showed that there was a significant difference in the influence of the two groups on pain levels by looking at the mean value for warm compresses of 17.00.